EFFICACY ASSESSMENT OF LARVICIDES IN THE CONTROL OF FLIES IN A LAYING INDUSTRIAL AVIARY - Moreira Pimenta, Guilherme; Rodrigues Ortega, Júlia; Místico de Azevedo, Alcinei; de Andrade Royo, Vanessa; Farias de Melo Júnior, Afrânio; Alves de Oliveira, Dario; Veiga Menezes, Elytania (Revista Unimontes Científica, 2022)
The eggs production through the confinement of chickens generates some inconveniences, among which the accumulation of manure, rich in organic matter that provides an environment conducive to the development and proliferation of Musca domestica. The objective of this work was to evaluate in a controlled environment the larvicidal efficacy in suppressing Musca domestica larvae. Material and methods used were the distribution of plastic trays exposed to oviposition in the farm sheds’ vicinity, applying the treatments in a controlled environment. Results shown that the isolated and intercropped treatments were effective in controlling the larvae. Concluding that the evaluation of the larvicidal efficacy of the Ciromanzine 50% principles; Triflumuron 48%; Ciromanzine 10%; and dolomitic limestone were effective in controlling larvae development in a controlled environment.